Annual report: NFPE II 1997 - BRAC (© BRAC, 2016)
1. Background 2. The programmer 3. NFPE going to scale 4. Management and supervision 5. NFPE in 1997 6. Quality in BRAC classroom 7. Impact of NFPE 8. Research and evaluation 8. Sharing experiences 9. Future directions.